Quasi-Solid Gel Electrolytes for Alkali Metal Battery Applications - Jiahui Lu; Yingying Chen; Yaojie Lei; Pauline Jaumaux; Hao Tian; Guoxiu Wang (Nano-Micro Letters)
Highlights This review explores the application of quasi-solid gel electrolytes (QSGEs) in alkali metal batteries (AMBs), emphasizing self-healing gels, flexible gels, biomimetic gels, and biomass gels. Each of these gel types brings unique advantages to the performance of AMBs. This review outlines future research directions, including synthesizing advanced QSGEs, in situ characterization techniques, and theoretical simulations to better understand and optimize these materials. It identifies critical areas for investigation, guiding researchers to optimize QSGEs in AMBs and enhance their application.